Dienogest in conjunction with GnRH-a for postoperative management of endometriosis - Ma, Ying; Wang, Wen-Xin; Zhao, Ye (Frontiers in Pharmacology, 2024)
Objective: The aim of this study is to assess the postoperative efficacy of the combined administration of dienogest (DNG) and gonadotropin-releasing hormone agonists (GnRH-a) in patients diagnosed with endometriosis (EMS), while acknowledging the extensive use of DNG in the extended therapeutic management of EMS. Methods: In this retrospective study, a cohort of 154 patients who underwent conservative surgical intervention for EMS were scrutinized. The cohort was stratified into two distinct groups based on their prescribed pharmacological regimens. Group A, 70 patients received postoperative oral administration of DNG at a dosage of 2 mg/day, whereas Group B, 84 patients underwent treatment involving 3 to 4 injections of GnRH-a post-surgery, followed by DNG therapy. Parameters assessed included pelvic pain visual analog scale (VAS) scores, quality of life metrics (EHP-5), and the incidence of adverse reactions within both groups. Results: Both groups exhibited sustained low VAS scores following the prescribed treatments. The predominant occurrence of adverse bleeding patterns manifested predominantly within the initial six months of the treatment. Notably, Group B demonstrated a significantly diminished of experiencing frequent and irregular bleeding in comparison to the DNG group (20.0%vs8.3%，12.9%vs3.6%, P < 0.05). The administration of GnRH-a did not exacerbate the impact on bone health. Subsequent to health promotion interventions, the incidence of weight gain in both groups declined to 7.1% during the 6-month follow-up (P < 0.05). Group B exhibited a 100% satisfaction rate with the treatment, concomitant with a noteworthy reduction in EHP-5 scores (P < 0.05). Patients with deep infiltrating endometriosis (DIE) nodules displayed marginally higher postoperative VAS scores than their non-DIE counterparts (0.89±0.96 vs. 0.49±0.78). However, with sustained medication use, pain scores within the DIE group exhibited a continual decrease, maintaining a low level of 0.29±0.67 at 12 months and beyond. Conclusion: The short-term adjunctive use of GnRH-a prior to DNG treatment postoperatively in patients with EMS proves efficacious in mitigating early adverse bleeding, enhancing patient adherence, and improving overall quality of life. Notably, this therapeutic approach demonstrates favorable safety profiles and is equally effective in patients with DIE.